Analisis Kinerja Ruas Jalan Kepanjen–Kendalpayak Kabupaten Malang Berdasarkan PKJI 2023 Dengan Pendekatan Segmentasi: Road Performance Analysis Of Kepanjen–Kendalpayak Malang Regency Based On Based PKJI 2023 Using A Segmentation Approach - Permana, Ari Widya; Mukhlis, Mukhammad (Media Ilmiah Teknik Sipil, 2026)
The Kepanjen–Kendalpayak road segment is a strategic collector road in Malang Regency, connecting residential areas with local and regional economic centers. Growing traffic flow without a comprehensive capacity evaluation poses a risk of significant service degradation. This study examines the operational performance of this road segment through capacity analysis, degree of saturation (DS), and level of service (LoS) using the Indonesian Highway Capacity Manual (PKJI 2023) for inter-urban roads. Field traffic surveys were conducted over two days across eleven segments spanning ±11.78 km, covering traffic volumes, road geometric data, and roadside friction classes. Results indicate that the peak hour occurs between 16:30–17:30 with a flow of 2208.8 pcu/hour, dominated by motorcycles. Segment capacities range from 2958.00 to 3340.80 pcu/hour, primarily influenced by lane width variation. The degree of saturation varies from 0.66 to 0.75, with three segments (STA 5+000, 8+000, and 9+000) exhibiting LoS D conditions. These findings demonstrate the necessity of a segment-based analytical approach for identifying critical performance points, providing a basis for targeted road management interventions.